ON THE POSSIBILITY OF EVALUATING THE TECTONIC FAULT ACTIVITY AT THE AKKUYU NUCLEAR POWER PLANT BY SAMPLE RADON MEASUREMENTS DURING ENVIRONMENTAL IMPACT ASSESSMENT - Sedin Vladimir L.; Ulyanov Vasiliy U. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Национальный исследовательский Московский государственный строительный университет», 2019)
Introduction. This paper sets out to justify the application of an innovative methodology for determining the rate of the tectonic fault activity of a rocky base using complex radon measurements under the conditions of the Akkuyu Nuclear Power Plant (NPP), Turkey. Materials and methods. The information contained in the Environmental Impact Assessment (EIA) chapters and sections relevant to both the site tectonics and methods for measuring radon in soil and groundwater was scrutinised. In addition, the experience of analogues studies in the Republic of Turkey was studied. Results. An analysis of experimental results enabled identification of individual subsoil areas of increased radon activity across the site under investigation. Additional comprehensive studies at the NPP site are recommended in combination with planned work aimed at clarifying the engineering and geological conditions regarding specific NPP buildings and structures (ED stage). Conclusions. The proposed additional studies are expected to provide a more comprehensive seismic protection of the NPP units under construction, thus enabling a long-term trouble-free operation of the completed NPP buildings and structures. In the framework of subsoil monitoring at the Akkuyu NPP, regulations on the application of the proposed methodology should be introduced in job descriptions. This technique appears to be prospective for seismic monitoring in other NPP sites located in areas with increased seismicity.
Keywords: ТУРЕЦКАЯ РЕСПУБЛИКА; АЭС «АККУЮ»; ИЗМЕРЕНИЯ РАДОНА В ПОЧВЕ; ИЗМЕРЕНИЯ РАДОНА В ВОДЕ БУРОВЫХ СКВАЖИН; РАДОН-МОНИТОР; REPUBLIC OF TURKEY; AKKUYU NPP; SOIL RADON MEASUREMENTS; BOREHOLE WATER RADON MEASUREMENTS; RADON MONITOR; 550.34: 551.243: 550.835.2